Karyotype of the invasive species Pterois volitans (Scorpaeniformes: Scorpaenidae) from Margarita Island, Venezuela - Nirchio, Mauro; Ehemann, Nicolas; Siccha-Ramirez, Raquel [UNESP]; Ron, Ernesto; Eduardo Perez, Julio; Rossi, Anna Rita; Oliveira, Claudio [UNESP] (Revista De Biologia Tropical, 2014)
The genus Pterois includes nine valid species, native to the Red Sea and Indian Ocean throughout the Western Pacific. P volitans and P miles are native to the Indo-Pacific, and were introduced into Florida waters as a result of aquarium releases, and have been recently recognized as invaders of the Western Atlantic and Caribbean Sea (Costa Rica to Venezuela). Thus far, cytogenetic studies of the genus Pterois only cover basic aspects of three species, including P volitans from Indo-Pacific Ocean. Considering the lack of more detailed information about cytogenetic characteristics of this invasive species, the objective of the present study was to investigate the basic and molecular cytogenetic characteristics of P volitans in Venezuela, and compare the results with those from the original distribution area. For this, the karyotypic characteristics of four lionfish caught in Margarita Island, Venezuela, were investigated by examining metaphase chromosomes by Giemsa staining, C-banding, Ag-NOR, and two-colour-Fluorescent in situ hybridization (FISH) for mapping of 18S and 5S ribosomal genes. Comparing the sequences of the 16S gene of the specimens analyzed, with sequences already included in the Genbank, we corroborated that our specimens identified as P volitans are in fact this species, and hence exclude the possibility of a misidentification of P miles. The diploid number was 2n=48 (2m+10sm+36a) with FN=60. Chromosomes uniformly decreased in size, making it difficult to clearly identify the homologues except for the only metacentric pair, and the pairs number two, the largest of the submetacentric series. C-banding revealed only three pairs of chromosomes negative for C-band, whereas all remaining chromosomes presented telomeric and some interstitial C-positive blocks. Only two chromosomes were C-banding positive at the pericentromeric regions. Sequential staining revealed Ag-NOR on the tips of the short arms of chromosome pair number two and the FISH assay revealed that 18S rDNA and 5S rDNA genes are co-located on this chromosome pair. The co-localization of 5S rDNA and 45S rDNA is discussed. Both constitutive heterochromatin and NOR location detected in samples examined in this study, differ from those reported for P volitans in previous analysis of specimens collected in Indian Ocean (Java), suggesting the occurrence of chromosome microrearrangements involving heterochromatin during the spread of P. volitans.

El género Pterois contiene nueve especies válidas, nativas del Mar Rojo y el Océano Índico en el Pacífico occidental. P. volitans y P. miles son nativas del Indo-Pacífico, y fueron introducidas en las aguas de Florida como resultado de la liberación de peces confinados en acuario y han sido reconocidas recientemente como invasoras en el Atlántico Occidental y Mar Caribe (Costa Rica hasta Venezuela). Los estudios citogenéticos realizados hasta ahora en el género Pterois cubren solamente aspectos básicos de tres especies que incluyen a P. volitans del océano Indo-Pacífico. Debido a la ausencia de información detallada sobre las características cromosómicas de esta especie invasora, el objetivo del presente estudio fue investigar las características citogenéticas en ejemplares de Venezuela mediante técnicas convencionales y moleculares y comparar los resultados con los reportados para el área de distribución original. Para ello, se investigaron las características cariotípicas mediante tinción con Giemsa, bandeo-C, impregnación con Nitrato de Plata (Ag-NOR) e hibridación fluorescente in situ (FISH) dual para localizar los genes ribosomales 18S rDNA y 5S rDNA en cuatro ejemplares de pez león capturados en la Isla Margarita, Venezuela. La comparación de secuencias del gen 16S de los especímenes analizados con secuencias ya incluidas en el Genbank permitieron corroborar la identificación de P. volitans excluyendo así la posibilidad de una identificación errónea de P. miles. El número diploide fue 2n=48 (2m+10sm+36a) con un FN=60. Los cromosomas presentaron tamaños que disminuyen de manera uniforme dificultando la identificación de homólogos, excepto el único par metacéntrico y el par cromosómico número 2. El bandeo-C reveló tres pares de cromosomas bandas-C negativos, mientras que los restantes presentaron bloques bandas-C positivos en posición telomérica y, en algunos casos, intersticial. Sólo dos cromosomas mostraron bandas-C pericentroméricas. La tinción secuencial reveló las Ag-NOR localizadas en los extremos de los brazos cortos del par número dos y el ensayo FISH demostró que los genes 18S rDNA y 5S rDNA se localizan en ese mismo par. Se discute la co-localización de los genes 5S rDNA y 18S rDNA. La distribución de la heterocromatina constitutiva y localización de las NORs en los peces examinados difirió de la reportada para ejemplares de P. volitans del Océano Índico (Java), sugiriendo que durante la propagación de P. volitans han ocurrido reorganizaciones cromosómicas que involucran la heterocromatina.
Cariotipo de la especie invasora Pterois volitans (Scorpaeniformes: Scorpaenidae) de Isla Margarita Island, Venezuela
Keywords: Karyotype; 18S and 5S ribosomal genes; 16S rRNA mitochondrial gene; Molecular identification; Invasive species; Cariotipo; Genes ribosomales 18S and 5S; Genes mitocondriales16S rARN; Identificación molecular; Especies invasoras